A case of probable oxybutynin-induced increase in liver enzymes - Alrawashdeh H; Madi L; Ahmed Elhada AH; Ahmed A; Serheed D (Dove Medical Press, 2018)
Haneen Alrawashdeh,1 Lama Madi,2 Arwa Hassan Ahmed Elhada,1 Afif Ahmed,1 Dhiaddin Serheed3 1Department of Pharmacy, Women Wellness and Research Center, Hamad Medical Corporation, Doha, Qatar; 2Department of Pharmacy, Qatar Rehabilitation Institute, Doha, Qatar; 3Department of Physical Medicine and Rehab, Qatar Rehabilitation Institute, Doha, Qatar Abstract: We describe the case of a 49-year-old male who presented to the emergency department with right-sided weakness and inability to speak. He was diagnosed with stroke and was admitted to Qatar Rehabilitation Institute after he was treated for the acute phase at Hamad General Hospital. As part of his management, he was started on oxybutynin 5 mg orally twice daily for the treatment of overactive bladder. Within a week, his liver enzymes started to increase. After a thorough medication review, oxybutynin was suspended as it was the only suspected medication to be responsible of this elevation in liver enzymes. When Naranjo Adverse Drug Reaction Probability Scale was used to assess the probability of an adverse drug reaction (ADR), a score of 6 was obtained indicating a “Probable” ADR. In conclusion, this is the first published report of oxybutynin-induced elevation in liver enzymes. Further reports are required to highlight this probable ADR and alert all health professionals about it. Keywords: oxybutynin, liver enzymes, alanine aminotransferase, aspartate aminotransferase, adverse drug reaction, liver injury